Damage tolerance (impact behaviour) of woven fabric nano composites - Lim, Andre Sian Lak. (2012)
Composites are fast gaining widespread popularity due to numerous benefits over steel and aluminium; however, they are still plagued by various weaknesses such as low impact and heat resistance.